Postoperative Ileal Perforation after a Cesarean Section: A New Presentation of Crohn’s Disease - Behrokh Sahebdel; Elham Rashidi; Hojatollah Raji; Fatemeh Golshahi; Saeed Aqavil-Jahromi (Case Reports in Clinical Practice, 2026)
Post-surgery ileus is a common complication after abdominal surgery. In cases of prolonged postoperative ileus lasting more than three days, underlying inflammatory bowel disease (IBD) should be considered. We present a 35-year-old woman who developed prolonged ileus after cesarean section, complicated by multiple ileal perforations that led to the diagnosis of Crohn’s disease. This case illustrates smallbowel perforation as the first clinical presentation of Crohn’s disease in the postpartum period.